Robust Optimization Design of Subway Underframe Based on Dual Response Surface - Yonghua LI; Huijie LI; Jian WANG; Pengpeng ZHI; Ziqiang SHENG; Baifa WANG (机车电传动)
In order to reduce the dispersion of the objective response due to uncertain factors in the subway underframe’s optimization process, a robust optimization design method based on dual response surface model was proposed. Firstly, Monte Carlo method was used to select the design variables which had great influence on the target response, and Latin hypercube sampling was used to get the sample points of the design variables and the target response. Then, the least square method was used to fit the sample points, and the polynomial response surface function of the target response was obtained, the mean and variance of the polynomial response surface function were estimated, and the response surface function of the mean and variance was obtained. Taking the minimum variance function as the optimization objective and the mean function as the constraints, the robust optimization model was established and solved by the interior point method. The results show that the anti-interference ability and strength of the structure is improved as well as the mass is reduced after the robust optimization of the double response surface model.